A New Subclass of Harmonic Univalent Functions Defined by q-calculus (Global Journal of Science Frontier Research, 2017)
In this paper we study a new subclass of harmonic univalent functions defined by q-calculus coefficient inequalities, distortion, bounds, extreme point, convolution, convex combination are determined for this class. Finally we discuss a class preserving integral operator and q- Jackson’s type integral for this class.
Keywords: analytic function; harmonic function; q-calculus; univalent function; integral operator